PROCEDURES FOR THE INVESTIGATION OF AIRCRAFT ACCIDENTS - B. P. Eliseev; V. Sannikov; A. D. Filin; A. Yu. Shatrakov (Научный вестник МГТУ ГА, 2016)
The article discusses current issues of the investigation of aircraft accidents. On the basis of regulatory documents it presents the scheme of the procedure of investigation of aircraft accidents based on the JCAO requirements and recommendations.